E-book Scenario in Malaysia Tertiary Education: A Case Study - P. F., Chong; Y. P., Lim; S. W., Ling (2008)
The advent of internet technology has made digital content widely accessible to everyone. However, previous studies showed that the uptake of e-books has been slow. This study attempts to investigate on the e-book usage of Multimedia University students. An online survey is conducted on 86 students to gauge their perception and acceptance of an e-book. Results showed that e-book usage is still not encouraging, where only 52.3% of the respondents have read an e-book. This paper sheds on some hardware and onscreen design factors that hinder the adoption of e-books in the institution.